Intravenous lidocaine enhances the efficacy of ondansetron and dexamethasone in postoperative vomiting prophylaxis among high-risk children - Jin-fei Xu; Ming-cheng Du; Yi Chen; Yang Hu; Xiang Long; Jing-jing Jiang; Yuan Gong (Scientific Reports)
Abstract A combination of dexamethasone, ondansetron, and total intravenous anaesthesia (TIVA) is recommended as prophylaxis for preventing postoperative vomiting (POV) in high-risk children. Implementing TIVA in paediatric patients undergoing anaesthesia presents challenges due to its excessive inter-individual variability and difficult estimation. Regarding lidocaine’s antiemetic effect in paediatric patients, incorporating lidocaine can mitigate POV in high-risk children. Among 204 children undergoing elective tonsillectomy (with/without adenoidectomy), those with postoperative vomiting score ≥ 4 was randomised into Group C (saline) and Group L (lidocaine). The primary outcome was POV incidence within the first 24 h after surgery. The POV incidence differed among 15 patients in Group C (14.7%) and 5 in Group L (4.9%) presenting with one or more episodes of POV (P = 0.019). The secondary outcome was the number of coughs within the first 30 min after surgery. The number of coughs within the first 30 min after surgery significantly differed between Group L (0 [0–0.125]) and Group C (1 [0–2]) (P = 0.007). Significant between-group differences in the time to extubation were also observed, with a 3-min longer time in Group L. A lower percentage of patients experienced adverse events in Group C (2.2%) compared with Group L (1.1%) (P = 0.567); no severe events occurred. Adding intravenous lidocaine to ondansetron and dexamethasone was effective in reducing the POV incidence and extubation coughs in high-risk children following volatile anaesthesia for tonsillectomy.